2015
DOI: 10.1111/jfr3.12186
|View full text |Cite
|
Sign up to set email alerts
|

On the impact of urbanization on flood hydrology of small ungauged basins: the case study of the Tiber river tributary network within the city of Rome

Abstract: The small ungauged basins of the highly urbanized area of the city of Rome are often the subject of critical flood conditions for the significant human‐made transformations. In this work the EBA4SUB framework, implementing the hydrogeomorphic width function instantaneous unit hydrograph rainfall run‐off model, and using digital elevation model, land use and synthetic precipitation as main input information, is applied for evaluating extreme hydrologic forcing conditions at the basic scale. The goal is to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 53 publications
2
28
0
1
Order By: Relevance
“…Actually, besides imperviousness, drainage efficiency has been widely reported to have significant influences in urban runoff [55,56]. It was reported that the efficiency of the drainage network control is more effective in reducing peak runoff than reducing the effective imperviousness [8,57]. Therefore, a more comprehensive consideration is needed for urban stormwater management with proper impervious configuration and reasonable drainage system arrangement in future urban design.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, besides imperviousness, drainage efficiency has been widely reported to have significant influences in urban runoff [55,56]. It was reported that the efficiency of the drainage network control is more effective in reducing peak runoff than reducing the effective imperviousness [8,57]. Therefore, a more comprehensive consideration is needed for urban stormwater management with proper impervious configuration and reasonable drainage system arrangement in future urban design.…”
Section: Discussionmentioning
confidence: 99%
“…These areas show a general reduction in terrain permeability and can affect the natural drainage pattern (May 1996;Chin 2006;Kang and Marston 2006;Hall et al 2014;Nardi et al 2015). Concerning agricultural areas, generally, we observed that vineyards and olive groves are set in anthropic terraced areas presenting bench structures with dry-stone walls, in terrain with steep to very-steep slope.…”
Section: Geospatial Processingmentioning
confidence: 82%
“…This research contributes to the development of alternative cost-effective parsimonious flood modeling approaches that can produce consistent results using largely available data, considering that floodplain morphology, and channel bathymetry specifically, is in constant change and measurements cannot be afforded periodically, becoming a challenge for both gauged and ungauged basins [43]. Results show that naturally surveyed cross sections can be replaced by synthetic geometry cross sections of rectangular shape maintaining a correct representation of channel slope (i.e., thalweg profile) and channel conveyance (i.e., channel flow area).…”
Section: Discussionmentioning
confidence: 99%